Neuromuscular and physiological responses to different training loads in Randori of elite judo athletes - Bruno T. Campos; Eduardo M. Penna; Alexandre T. Katsuragi; Leonardo Porto; Fúlvio K. Miyata; Maicon Rodrigues Albuquerque; Victor S. Coswig; Carolina F. Wilke; Luciano S. Prado (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: To compare two different randori structure (high volume and short pauses - TRAD training vs low volume with long pauses - COMP training) in the neuromuscular and metabolic responses of elite judo athletes. Methods: The first situation (TRAD) consisted of 12 randoris of 5 minutes with 45 seconds rest, and the other situation (COMP), consisted of 6 randoris of 5 minutes with 10 minutes between them. Physiological (Blood Lactate and Creatine Kinase), neuromuscular (Countermovement Jump and Medicine Ball Throws) and perceptive variables (Rating Perceived Exertion) were measured before and at the end of the sessions. Results: The subjective perception of effort at the end of the training was significantly higher in the TRAD training type (TRADpost: 8.1 ± 0.9 AU; COMPpost: 6.6 ± 1.5 AU, p <0.001). Blood lactate concentration (TRADpost: 6.4 ± 2.2 mmol/L; COMPpost: 8.1 ± 2.9 mmol/L; p <0.001), CMJ height (TRADpost: 36.2 ± 4.6 cm; COMPpost: 35.9 ± 4.3 cm, p = 0.012) and upper limb power performance (TRADpost: 6.4 ± 0.9 m; COMPpost: 6.3 ± 0.9 m p = 0.03) were significantly higher at the end of the two training sessions compared to their start, but there are no group effect. There is group effect in CK (TRADpost: 490.7 ± 273.5 UŁ; COMPpost: 357.4 ± 203.8 UŁ; p <0.001). Conclusions: This study demonstrated that TRAD and COMP Judo training induced similar physical demands, and both seem to not be enough to reach higher intensities, which made them distant methods of competitive reality.